Steamboat ORA navigating Five Finger Rapids on the Yukon River, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: ""Ora" lining up Five Finger Rapids" Original image in Hegg Album 21, page 40.